A literature review on port sustainability and ocean's carrier network problem. (June 2016) - Sislian, L.; Jaegler, A.; Cariou, P.
Abstract: In the present paper, we aim to review the maritime literature of two interrelated concepts: Port Sustainability and Ocean's Carrier Network Problem (OCNP). The past literature did not establish a clear relationship between these two concepts, as the sustainability concept is a relatively recent approach in the maritime literature, and still a gap exists in this field. This study will have the objective to review the port sustainability concept and then to relate it to the OCNP, in order to reach a conceptual framework which will integrate port sustainability indicators in the OCNP. This will be achieved by interrelating them using the triple bottom line concept and focusing solely on the environmental approach. The conceptual framework will be our future perspective to be achieved through our upcoming work.